Arctic Fox (Alopex Lagopus) Dens in the Disko Bay Area, West Greenland - Nielsen, Sussie M.; Pedersen, Vivi; Klitgaard, Bente Bang (ARCTIC, 1994)
Seventeen arctic fox (Alopex lagopus) dens in the Disko Bay area, West Greenland are described regarding location, type, size and vegetation cover. The dens were found in ridges, screes and level ground, mainly of dwarf-scrub heath. The mean number of entrances was 17.8±18.4 SD (range 1-63), with more than half of the dens having fewer than 10 entrances. For dens in slopes, there was a prevalence for south-facing slopes, but for dens with an open exposure, entrances were most frequently oriented towards the north and east. The dens were not found to be lush green, as reported from several other areas. A visual difference between the den vegetation and the surrounding vegetation could only be recognized at a few den sites. A vegetation analysis revealed a significant difference between the den and the surrounding area in the occurrence of eight plant species. Among the species occurring more frequently on the den than in the adjacent area, Stellaria longipes was the most conspicuous because of its white flowers. This species is therefore suggested as a guide species in the search for new dens in the Disko Bay area. Dens with recent fox activity were larger and more conspicuous than dens without sign of recent activity.Key words: Arctic fox, Alopex lagopus, den site, den vegetation, Disko Bay, West Greenland On donne une description des terriers de 17 renards arctiques (Alopex lagopus) dans la région de la baie de Disko, à l'ouest du Groenland, selon l'emplacement, le type, la dimension et le couvert végétal. Ces terriers avaient été creusés dans des crêtes, des éboulis et en terrain plat, surtout dans des zones où la végétation se composait d'arbustes nains. Le nombre d'entrées était de 17,8, avec un écart-type de 18,4 (gamme de 1 à 63), plus de la moitié des terriers ayant moins de 10 entrées. Les terriers creusés dans les talus étaient plutôt exposés au sud, mais ceux qui étaient ouverts avaient leurs entrées orientées le plus fréquemment vers le nord et vers l'est. On n'a pas trouvé de végétation très dense ...